Rasgos morfológicos alrededor de la Isla del Coco y de sus montes submarinos vecinos, Pacífico de Costa Rica - Lizano, Omar G. (Revista de Biología Tropical, 2012)
Morphological features around Isla del Coco and its adjacent seamounts, Pacific Costa Rica. The UNESCO GEBCO-08 bathymetric data was used to study the marine provinces around Isla del Coco. Seamounts with depths of less than 1000m from the sea surface were analyzed. Seamounts southward, southeastward and westward of the island, were identified at depths of 300m from the sea surface, and with heights up to 2700m from the marine bottom. The ecological interconnection of these mountains with Isla del Coco has to be effective, as it could also be within the biological corridor of Eastern Tropical Pacific. A better resolution study around Isla del Coco was done to identify details of the insular platform. A seamount to 14.8km northeast of the island was found, with measured depths of 30-40m, and so far, not reported. This feature explains the presence of fishermen around this site, which is known by them as a place with high productivity. Although more studies are needed, the limits and environmental policies should be modified so as to adequately protect these seamounts, which probably have an important ecological connection with Isla del Coco. Citation: Lizano, O.G. 2012. Rasgos morfológicos alrededor de la Isla del Coco y de sus montes submarinos vecinos, Pacífico de Costa Rica. Rev. Biol. Trop. 60 (Suppl. 3): 43-51. Epub 2012 Dec 01